Analisis Strategi Pemasaran Dengan Menggunakan Analisis SWOT dalam Meningkatkan Volume Penjualan Di Toko Terang Abadi di Kecamatan Papalang - Muhammad Risal; Ramli S; Suharlina (Fakultas Ekonomi, Universitas Muslim Indonesia, 2025)
Marketing strategy plays a highly strategic role in driving the business growth of Toko Terang Abadi. Amid increasingly competitive market conditions, it serves as a vital tool for enhancing the company’s economic value. By implementing appropriate and innovative strategies, Toko Terang Abadi has the potential to attract new customers while maintaining the loyalty of existing ones. This study was conducted at Toko Terang Abadi, located in Papalang District, with the aim of formulating an effective marketing strategy to increase sales volume. A quantitative approach was employed, with Toko Terang Abadi as the subject and its marketing strategy as the object of the research. The data collected were analyzed using the SWOT method to identify the company’s strengths, weaknesses, opportunities, and threats. The results of the SWOT analysis indicate that Toko Terang Abadi is positioned in Quadrant I, signifying a strong internal position combined with substantial external opportunities for business expansion. This favorable position suggests that the company is well-suited to adopt an aggressive strategy—one that emphasizes active business expansion and optimizes growth potential by leveraging internal strengths to seize market opportunities. Based on these findings, it is recommended that the management of Toko Terang Abadi continue to pursue business expansion by opening new branches in other regions. Such initiatives are expected to strengthen the company's market position and provide a competitive advantage over other retail businesses.